OBYEK DAN ANALISIS POTENSI DAYA TARIK WISATA ALAM TAMAN WISATA ALAM SICIKEH-CIKEH KABUPATEN DAIRI PROPINSI SUMATERA UTARA - , AISYAH DWI PUJI A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is a country rich in biodiversity, with uniqueness and authenticity of traditional culture, the beauty of the landscape and natural phenomena, which is the potential for the development of nature tourism activities. North Sumatra has considerable tourism potential that has not been optimally developed, especially over the location and various types of tourism in Dairi. Nature park Sicikeh-cikeh is one of nature tourism potential that has not managed optimally. Study was conducted to assess the potential of objects and natural tourist attraction, which is in-cikeh Sicikeh Nature, which is in the Pancar Nuli village, Sidikalang sub district, Dairi regency . Potential data capture objects and natural tourist attraction was done by direct observation, interviews with stakeholders and secondary data collection. The components to be assessed is a tourist attraction that includes beauty, uniqueness, authenticity and quality of each potential view of the existing tourist attraction